PSYCHOPHARMACOLOGY: A HISTORICAL APPROACH - Torres Bares, Carmen; Escarabajal Arrieta, Mª Dolores (Anales de Psicología / Annals of Psychology, 2005)
Psychopharmacology can be defined as a scientific discipline that studies drugs able to modify the behaviour and the mental function through its action on the neuroendocrine system. Pharmacology, biochemistry, psychiatry and psychology share their interest for this multidisciplinary field of knowledge, devoted to the analysis of the substances that alter those functions of the nervous system that are shown on the organism’s behaviour.This paper reviews the theoretical concept of psychopharmacology, and the main historical events that occurred in clinical psychiatry, laboratory pharmacological research, and behavioural studies conducted in both animals and human beings.